A FRET‐Based Near‐Infrared Fluorescent Probe for Ratiometric Detection of Cysteine in Mitochondria. (14th June 2019) - Xia, Shuai; Zhang, Yibin; Fang, Mingxi; Mikesell, Logan; Steenwinkel, Tessa E.; Wan, Shulin; Phillips, Tyler; Luck, Rudy L.; Werner, Thomas; Liu, Haiying
Abstract: We report a near‐infrared fluorescent probe A for the ratiometric detection of cysteine based on FRET from a coumarin donor to a near‐infrared rhodamine acceptor. Upon addition of cysteine, the coumarin fluorescence increased dramatically up to 18‐fold and the fluorescence of the rhodamine acceptor decreased moderately by 45 % under excitation of the coumarin unit. Probe A has been used to detect cysteine concentration changes in live cells ratiometrically and to visualize fluctuations in cysteine concentrations induced by oxidation stress through treatment with hydrogen peroxide or lipopolysaccharide (LPS). Finally, probe A was successfully applied for the in vivo imaging of Drosophila melanogaster larvae to measure cysteine concentration changes. Abstract : See the light : A fluorescent probe based on coumarin as a donor and a near‐infrared rhodamine acceptor has been developed for the sensitive ratiometric detection of Cys and visualization of fluctuations in Cys concentrations induced by oxidation stress through treatment with hydrogen peroxide or lipopolysaccharide. The probe was successfully applied for the in vivo imaging of cysteine concentration changes in D. melanogaster larvae.